(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of microsurgical varicocelectomy in the treatment of varicocele at Viet Duc University Hospital during the period 2016-2024. Subjects and methods: A retrospective descriptive study was conducted on 746 patients diagnosed with varicocele and treated with microsurgical varicocelectomy at Viet Duc University Hospital between 2016 and 2024. Clinical characteristics, paraclinical findings, and treatment outcomes were collected from medical records and analyzed using SPSS version 22.0. Results: The mean age of the patients was 27.21 ± 8.43 years (range 10-61 years). Left-sided varicocele accounted for 76.2% of cases. Grade III varicocele was the most common presentation, observed in 74.9% of patients, while venous reflux on Doppler ultrasonography was detected in 78%. The mean spermatic vein diameter before surgery was 2.70 ± 0.63 mm at rest and 3.28 ± 0.67 mm during the Valsalva maneuver. One month after surgery, these values decreased to 2.25 ± 0.64 mm and 2.49 ± 0.62 mm, respectively. The reduction in spermatic vein diameter after surgery was statistically significant (p < 0.05). A good treatment outcome was achieved in 95.6% of patients, while 4.4% had a fair outcome. Conclusion: Microsurgical varicocelectomy is a safe and effective treatment for varicocele. The procedure resulted in a significant reduction in spermatic vein diameter on Doppler ultrasonography and demonstrated a high success rate of 95.6%, supporting its important role in the management of varicocele.